NELSON FARIA AND THE TOPICS IN BRAZILIAN JAZZ: A CASE STUDY - da Silva Cortez, Alexandre (Revista Gênero e Interdisciplinaridade, 2023)
This communication deals with the analysis of an improvisation by guitarist Nelson Faria in the song Incompatibilidade de Gênios by João Bosco and Aldir Blanc recorded on the album Nelson Faria & Frankfurt Radio Bigband – Live In Frankfurt. Before, we will present a brief historical context of the electric guitar problem in Brazil followed by a biographical synthesis of Nelson, later we will make the harmonic and melodic analysis, followed by an analysis using the theory of topics applied to popular music, seeking to identify aspects that point to a friction of musicalities present in Brazilian instrumental music or Brazilian jazz and contribute to the debate of musicology in the area. The present work is part of a larger research at master’s level with incipient results.